Analysing Skills Needed For Doctoral Researchers: A Systematic Literature Review - Pandey, Parul; Kaushal, Urvashi (Journal of Engineering Education Transformations, 2025)
The skill development of doctoral researchers has been the subject of several research studies conducted in the last few decades. However, there’s been a dearth of a systematic literature review in the literature pertaining to doctoral researchers. Hence, the aim of this first-of-its-kind SLR on doctoral researchers belonging to STEM, Management, and Humanities is to analyse skills needed for doctoral researchers by preparing a consolidated list of skills along with their rankings. This SLR has also highlighted the limitations of the research methodology used in the studies and the implications for the stakeholders involved in the process of researcher development. This systematic literature review (SLR) included 48 empirical and theoretical research studies synthesized in a comprehensive manner, and the findings revealed: a) a consolidated list of 35 skills along with their rankings for doctoral researchers; b) 40% studies had a sample size below 50, and there’s a dearth of studies having a mixed method approach; c) the formulation of a list of skills can help the stakeholders design and incorporate programs to inculcate these skills in doctoral researchers and ensure successful completion of PhD, reduce attrition rates, and increase researchers’ employment in academia and industry. It is recommended that future studies have a standalone SLR with empirical studies for doctoral researchers to lend credibility, validity, and generalizability to the study and produce standard results. Additionally, preparing a similar standalone study for researchers belonging to STEM, Management, and Humanities is recommended.